Are homeostatic mechanisms aiding the reconstitution of the T-cell pool during lymphopenia in humans? - Baliu-Piqué, Mariona; Tesselaar, Kiki; Borghans, José A. M. (Frontiers in Immunology, 2022)
A timely recovery of T-cell numbers following haematopoietic stem-cell transplantation (HSCT) is essential for preventing complications, such as increased risk of infection and disease relapse. In analogy to the occurrence of lymphopenia-induced proliferation in mice, T-cell dynamics in humans are thought to be homeostatically regulated in a cell density-dependent manner. The idea is that T cells divide faster and/or live longer when T-cell numbers are low, thereby helping the reconstitution of the T-cell pool. T-cell reconstitution after HSCT is, however, known to occur notoriously slowly. In fact, the evidence for the existence of homeostatic mechanisms in humans is quite ambiguous, since lymphopenia is often associated with infectious complications and immune activation, which confound the study of homeostatic regulation. This calls into question whether homeostatic mechanisms aid the reconstitution of the T-cell pool during lymphopenia in humans. Here we review the changes in T-cell dynamics in different situations of T-cell deficiency in humans, including the early development of the immune system after birth, healthy ageing, HIV infection, thymectomy and hematopoietic stem cell transplantation (HSCT). We discuss to what extent these changes in T-cell dynamics are a side-effect of increased immune activation during lymphopenia, and to what extent they truly reflect homeostatic mechanisms.